Factors that influence internet banking adoption among UiTM Melaka City Campus undergraduates / Nabila Emira Abdul Hamid - Abdul Hamid, Nabila Emira (Faculty of Business and Management, 2015)
This thesis reports the findings of a study issues concerning the adoption of internet banking among UiTM Melaka City Campus undergraduates. It is becoming critical for bank managers to understand their customers in order to deliver services effectively. This study investigates students’ adoption within the context of Malaysia Internet Banking services and research framework on the extension of Technology Acceptance Model (TAM). Theory was developed to identify factors that would influence the adoption of Internet banking. The framework includes Perceived usefulness, Perceived ease of use and Perceived credibility. Survey was conducted to gather the data. 150 respondents were selected as sample using convenience-sampling method. Data analysis was then based on 134 valid responses. Results show that Perceived usefulness and Perceived ease of use significantly influence student to adopt Internet banking while there is no significant relationship with Perceived credibility. The findings would be useful to theoretical development in Internet banking.